Linking Empowering Leadership and Organizational Citizenship Behavior Toward Environment: The Role of Psychological Ownership and Future Time Perspective - Jiang, Meiqin; Wang, Huaying; Li, Mingze (Frontiers in Psychology, 2019)
Organizations are confronted with increasing social responsibility to contribute to the environmental sustainability. Employee organizational citizenship behavior toward environment is considered essential to organizational environment performance. Drawing upon theory of psychological ownership, the study investigated the effect of empowering leadership on employee organizational citizenship behavior toward environment by a sample of 374 employees in China. By using bootstrapping technique in SPSS 25 to test our proposed moderated mediation model, results demonstrated a positive relationship between empowering leadership and organizational citizenship behavior toward environment through the mechanism of employee psychological ownership. Further, we found that the indirect effect is stronger when employees hold high rather than low future time perspective. The theoretical implications for sustainability literature and practical implications for organizations striving for environmental sustainability are discussed.